Representation of Gender Equality in Arabic Textbooks for Junior Schools in Indonesia - Sanah, Siti; Fauzia, Eva Lathifah; Ardiansyah, Ade Arip; Lutfiani, Yuni (International Journal of Language Education, 2025)
Gender equality is a consideration that must be addressed in the preparation of learning materials. Therefore, analyzing textbook learning materials from a gender equality perspective is essential. The purpose of this study is to identify the reality of gender equality in the learning materials of the 2020 Arabic textbook for MTs (Ministry of Religion) and the 2017 Arabic textbook for SMP (Ministry of Education and Culture). This study employs a qualitative method, using documentation and quotation techniques to collect data and content analysis to analyze the data. The results indicate that both textbooks represent gender equality in their instructional content, as evidenced by the identification of gender equality themes within the instructional content, such as: equality in roles and relationships, equality in rights and opportunities, equality in economic and social development, and equality in education and potential development. Additionally, gender equality subjects were found in various forms, such as: names of people, isim mudzakkar and muannats, isim dhamir (ghaib, mukhatab, dan mutakallim ma’al ghair), isim isyaroh lil ‘aqil (qorib and ba’id), isim maushul lil ‘aqil, and fi’il mudzakkar and muannats. These results can serve as a reference for improving the quality of Arabic-language teaching materials to be gender-equitable, thereby ensuring that students' understanding of gender equality in these materials is balanced. This study recommends developing Arabic-language teaching materials grounded in gender equality.